2019
DOI: 10.2183/pjab.95.018
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar-type ATPase: A proton pump to lysosomal trafficking

Abstract: Vacuolar-type ATPase (V-ATPase), initially identified in yeast and plant vacuoles, pumps protons into the lumen of organelles coupled with ATP hydrolysis. The mammalian counterpart is found ubiquitously in endomembrane organelles and the plasma membrane of specialized cells such as osteoclasts. V-ATPase is also present in unique organelles such as insulin secretory granules, neural synaptic vesicles, and acrosomes of spermatozoa. Consistent with its diverse physiological roles and unique localization, the seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 87 publications
3
78
0
1
Order By: Relevance
“…An acidic pH is important for many physiological processes, such as renal acidification, bone resorption, and sperm maturation. V-ATPases localize to the plasma membrane, endosomes, and membrane vesicles and play an important role in proton homeostasis 1 4 . V-ATPase is involved in autophagy 5 , metabolism 6 , 7 , and neurotransmitter secretion 3 .…”
Section: Introductionmentioning
confidence: 99%
“…An acidic pH is important for many physiological processes, such as renal acidification, bone resorption, and sperm maturation. V-ATPases localize to the plasma membrane, endosomes, and membrane vesicles and play an important role in proton homeostasis 1 4 . V-ATPase is involved in autophagy 5 , metabolism 6 , 7 , and neurotransmitter secretion 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nutrients and growth factors can drive lysosomes toward the plasma membrane, whereas starvation results in lysosomes moving toward perinuclear localization [46,47]. Vacuolar-type proton pumping ATPase (V-ATPase) is a ubiquitous enzyme responsible for H + transport across membranes and acidification of cellular compartments in animals [48]. The phosphate bond energy of ATP is thus converted to a proton gradient across the membrane through the mechanical rotation of subunits.…”
Section: Autophagic Fluxmentioning
confidence: 99%
“…The phosphate bond energy of ATP is thus converted to a proton gradient across the membrane through the mechanical rotation of subunits. The proton pumping action of lysosomal V-ATPases results in the generations of an acidic lumen and proton gradient of lysosomes, which are essential for normal functions of lysosomes [48]. A recent study in our lab has revealed that inhibition of V-ATPase activity remarkably attenuated lysosome function, leading to autophagic deficiency and podocyte dedifferentiation [26].…”
Section: Autophagic Fluxmentioning
confidence: 99%
“…Also, the fact that the annotations for SPERM did not contain specificities is unsurprising: After all, many sperm-expressed proteins exert their multiple functions in diverse tissues [Schumacher and Herlyn, 2018]. Nevertheless, SPERM also exhibited clear connections to re-production, as exemplified by TSG10 (TSGA10), which is mainly expressed in sperm tail, and VATE2 (ATP6V1E2; alias VMA4), which participates in acrosomal acidification [Sha et al, 2018;Futai et al, 2019]. However, most such associations existed for the protein set representing the organ of spermiogenesis, TESTIS.…”
Section: General Characteristics Of Protein Sets and Testis Specialtiesmentioning
confidence: 99%